Akibat Hukum Perceraian Terhadap Harta Benda Perkawinan - Sugih Ayu Pratitis (DOKTRINA: JOURNAL OF LAW, 2019)
The emergence of the problem of joint property in a marriage is usually when there is a divorce between husband and wife, or when the divorce process is taking place in the Religious Court. The purpose of the study is to examine the position of joint property in marriage according to Islamic law and the provisions of the legislation and the legal consequences of divorce on marital property. The research method used is a type of normative research where research is carried out by first researching the materials that are in accordance with the problem to be studied. The result of this research is that the position of husband and wife property obtained in marriage is shared property except personal property which is under the marriage will be the personal rights of each husband or wife. While due to divorce between husband and wife, the assets obtained during marriage are divided in half for the husband and half for the wife. The method for resolving cases of sharing of shared assets at the Religious Court is if the divorce has been approved by a judge, then a husband and wife can submit a request for sharing of shared assets in accordance with applicable law. And if a divorced husband and wife do not want to carry out the distribution of shared assets, then one of the parties can submit a request for execution in the Religious Court to force those who do not want to carry out the decision in accordance with what was decided by the Religious Court.